Physiology of the Nitrite-Oxidizing Bacterium Candidatus Nitrotoga sp. CP45 Enriched From a Colorado River - Lantz, Munira A.; Boddicker, Andrew M.; Kain, Michael P.; Berg, Owen M. C.; Wham, Courtney D.; Mosier, Annika C. (Frontiers in Microbiology, 2021)
Nitrogen cycling microbes, including nitrite-oxidizing bacteria (NOB), perform critical ecosystem functions that help mitigate anthropogenic stresses and maintain ecosystem health. Activity of these beneficial nitrogen cycling microbes is dictated in part by the microorganisms’ response to physicochemical conditions, such as temperature, pH, and nutrient availability. NOB from the newly described Candidatus Nitrotoga genus have been detected in a wide range of habitats across the globe, yet only a few organisms within the genus have been physiologically characterized. For freshwater systems where NOB are critical for supporting aquatic life, Ca. Nitrotoga have been previously detected but little is known about the physiological potential of these organisms or their response to changing environmental conditions. Here, we determined functional response to environmental change for a representative freshwater species of Ca. Nitrotoga (Ca. Nitrotoga sp. CP45, enriched from a Colorado river). The physiological findings demonstrated that CP45 maintained nitrite oxidation at pH levels of 5-8, at temperatures from 4-28˚C, and when incubated in the dark. Light exposure and elevated temperature (30˚C) completely halted nitrite oxidation. Ca. Nitrotoga sp. CP45 maintained nitrite oxidation upon exposure to four different antibiotics, and potential rates of nitrite oxidation by river sediment communities were also resilient to antibiotic stress. We explored the Ca. Nitrotoga sp. CP45 genome to make predictions about adaptations to enable survival under specific conditions. Overall, these results contribute to our understanding of the versatility of a representative freshwater Ca. Nitrotoga sp. Identifying the specific environmental conditions that maximize NOB metabolic rates may ultimately direct future management decisions aimed at restoring impacted systems.